Existence and Uniqueness of Common Fixed Point on Complex Partial b-Metric Space. (27th February 2022) - Gnanaprakasam, Arul Joseph; Mani, Gunaseelan; Aphane, M.; Gaba, Yaé U.
Abstract : In this study, we establish the existence and uniqueness of common fixed point on complex partial b -metric space. An example and application to support our result is presented. The fourth author Y. U. Gaba would like to dedicate this publication to his wife, Clémence A. Epse G., in celebration of her 33rd birthday